Determining Gases In Steel And The Deoxidation Of Steel - J. R. Cain (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
ROLE OF GASES IN FERROUS -METALLURGICAL PROCESSES IN every process for making steel there are one or more stages where the metal is exposed to gas of one kind or another. Thus, in the open-hearth furnace, the carbon dioxide and water vapor in the products of combustion are oxidizing toward the ferrous and manganous oxides in the slag, tending to convert these to higher oxides; the higher oxides then oxidize the steel, so that indirectly the products of combustion are oxidizing toward the steel. In the Bessemer process, there is direct contact of air and steel; also, the water vapor in the air blown into the converter is continually decomposed by the molten steel, yielding hydrogen and ferrous oxide, both of which are in part taken up by the metal. In the electric-furnace processes, there is always more or less air in contact with the slag covering the metal, and this air and the gaseous reaction products from it are dissolved in the slag to some extent and thus transmitted in part to the steel. In the crucible processes, there is always entrapped air in the charges and the crucibles are more or less permeable to the gaseous products of combustion from the furnace. In all the processes of manufacture, the molten metal is exposed to air while tapping into ladles and ingot molds and has an opportunity to saturate itself with air or with gaseous or solid products generated by chemical reactions between air and steel. Sieverts1 has shown that molten metals require but a few seconds to saturate themselves with a surrounding gas. No one familiar with the operations at a steel plant needs to be reminded of the important role that gases play at all stages. The familiar "boil" of open-hearth furnaces, due to evolution of carbon monoxide when iron ore is added to the molten steel; the spectacular operation of the Bessemer converter brought about entirely by a gaseous reagent; the almost magic effect of small quantities of silicon manganese or